If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(d + 2) = 12 Reorder the terms: -6(2 + d) = 12 (2 * -6 + d * -6) = 12 (-12 + -6d) = 12 Solving -12 + -6d = 12 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -6d = 12 + 12 Combine like terms: -12 + 12 = 0 0 + -6d = 12 + 12 -6d = 12 + 12 Combine like terms: 12 + 12 = 24 -6d = 24 Divide each side by '-6'. d = -4 Simplifying d = -4
| -3(2+y)=48 | | 17x^2-13x-2=0 | | 7c-5d-6c+4d= | | 81m^2-64m^2/9x-8x | | y=-3x(-2) | | a(12+8)=54 | | (ax-12b)(ax+12b)= | | (-2xy)(-6x)= | | ax+x= | | (a-5x/2a)-(8a-3x/2a) | | 15+2(y+x)=37 | | Y^4+21y^2-72=0 | | X-(0.25*X)=27 | | 180=(180-(7x-4))+(7x-4) | | 600x-.5x^2-(100x+2x^2)= | | 2(0)+3(0)+z=6 | | 2(x)+3(0)+0=6 | | 2(0)+3(y)+0=6 | | 4r^4*3r^4= | | u/6=v | | 2(x)+3(0)+(0)=6 | | 2a+7=6 | | 0+3(0)+2(z)=6 | | 0+3(y)+2(0)=6 | | Log(5-6x)=1 | | x+3(0)+2(0)=6 | | -6x-5y=34 | | -10+(-11)= | | 2(0)+3(0)-6(z)=30 | | 2(0)+3(y)-6(0)=30 | | 5+(-20)= | | 2(x)+3(0)-6(0)=30 |